Probiotics in Medicine: A Long Debate - Stavropoulou, Elisavet; Bezirtzoglou, Eugenia (Frontiers in Immunology, 2020)
During the last years probiotics gained the attention of clinicians for their use in the prevention and treatment of multiple diseases. Probiotics main mechanisms of action include enhanced mucosal barrier function, direct antagonism with pathogens, inhibition of bacterial adherence and invasion capacity in the intestinal epithelium, boosting of the immune system and regulation of the central nervous system. It is accepted that there is a mutual communication between the gut microbiota and the liver, the so-called “microbiota-gut-liver axis” as well as a reciprocal communication between the intestinal microbiota and the central nervous system through the “microbiota-gut-brain axis.” Moreover, recently the “gut-lung axis” in bacterial and viral infections is considerably discussed for bacterial and viral infections, as the intestinal microbiota amplifies the alveolar macrophage activity having a protective role in the host defense against pneumonia. The importance of the normal human intestinal microbiota is recognized in the preservation of health. Disease states such as, infections, autoimmune conditions, allergy and other may occur when the intestinal balance is disturbed. Probiotics seem to be a promising approach to prevent and even reduce the symptoms of such clinical states as an adjuvant therapy by preserving the balance of the normal intestinal microbiota and improving the immune system. The present review states globally all different disorders in which probiotics can be given. To date, Stronger data in favor of their clinical use are provided in the prevention of gastrointestinal disorders, antibiotic-associated diarrhea, allergy and respiratory infections. We hereby discuss the role of probiotics in the reduction of the respiratory infection symptoms and we focus on the possibility to use them as an adjuvant to the therapeutic approach of the pandemic COVID-19. Nevertheless, it is accepted by the scientific community that more clinical studies should be undertaken in large samples of diseased populations so that the assessment of their therapeutic potential provide us with strong evidence for their efficacy and safety in clinical use.